2019
DOI: 10.1167/iovs.18-26426
|View full text |Cite
|
Sign up to set email alerts
|

Implicating Dysbiosis of the Gut Fungal Microbiome in Uveitis, an Inflammatory Disease of the Eye

Abstract: In this study, the gut fungal microbiome of uveitis (UVT) patients was generated and compared with healthy controls (HC) to identify dysbiosis in UVT patients and ascertain the role of gut fungal microbiome in disease pathology. METHODS. In the present study, gut fungal microbiomes were analyzed in the fecal samples of HC (n ¼ 24) and UVT patients (n ¼ 14) using high-throughput Illumina sequencing of ITS2 region of the fungal ribosomal RNA. QIIME and R software were used for data analysis. RESULTS. The gut fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 50 publications
(83 reference statements)
1
33
0
4
Order By: Relevance
“…Horai et al [6] and Huang et al [7] were among the first to demonstrate that dysbiosis in the gut microbiome is associated with uveitis in mice and in uveitis patients respectively. This observation of gut microbiome dysbiosis in uveitis patients was further confirmed by several others [8,9] including in Behcet′s disease patients with uveitis [10] and in patients with ocular mucosal disease [11], as well as in age-related macular degeneration (AMD) in mice and in AMD patients [12,13]. In our recent studies, we demonstrated dysbiosis in gut bacterial and fungal microbiomes in patients with ocular inflammatory diseases like uveitis [8,9], bacterial keratitis [14], and fungal keratitis [15].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Horai et al [6] and Huang et al [7] were among the first to demonstrate that dysbiosis in the gut microbiome is associated with uveitis in mice and in uveitis patients respectively. This observation of gut microbiome dysbiosis in uveitis patients was further confirmed by several others [8,9] including in Behcet′s disease patients with uveitis [10] and in patients with ocular mucosal disease [11], as well as in age-related macular degeneration (AMD) in mice and in AMD patients [12,13]. In our recent studies, we demonstrated dysbiosis in gut bacterial and fungal microbiomes in patients with ocular inflammatory diseases like uveitis [8,9], bacterial keratitis [14], and fungal keratitis [15].…”
Section: Introductionsupporting
confidence: 82%
“…Implicating a microbiome in the pathogenesis of a disease has been best studied in immune-mediated diseases [44], inflammatory diseases [2,3], cancers, and mental disorders [4], ocular diseases like uveitis [6,7,8,9,10,45], ocular mucosal disease [11], age-related macular degeneration [13], as well as bacterial and fungal keratitis [14,15]. These findings suggest a prime role for the gut bacterial microbiome in human health and disease irrespective of the disease location in the human body [5].…”
Section: Discussionmentioning
confidence: 99%
“…These observations of increase in pathogenic fungi in T2DM are also similar to ones with allergic asthma [85] implying that such changes may be common to several diseases mediated by mast cells and aggravate allergic inflammation [86]. The only studies available on ocular diseases include gut mycobiome changes in UVT [59], BK [18] and FK [19]. When we compared the BK and UVT mycobiomes, 18 identical fungi were identified either at the genera or higher level exhibited a decrease in abundance and included fungi that were beneficial to HC due to their anti-inflammatory or anti-pathogenic effects [18,59].…”
Section: Plos Onementioning
confidence: 58%
“…Since these studies were undertaken simultaneously, a few of the individuals in the HC cohort were identical. The data of 13 of 30 HC samples were reported in our earlier reports [18,19,59]. Fecal samples were collected by the study subjects at home in a sterile container (HiMedia, India) without any storage medium and delivered within 4 hours to LVPEI at room temperature.…”
Section: Plos Onementioning
confidence: 99%
“…(46). Members [wuc] of the Pleosporales order, however, have been associated with healthy mucosa in studies involving the occurrence of UV light-derived eye inflammation (96), as well as in the study on CD described by 82.…”
Section: Discussionmentioning
confidence: 99%